The Road to Resilience Rethinking Responses to Food Crises - Swinnen, Johan (2023)
Johan Swinnen GLOBAL FOOD POLICY REPORT IFPRI’s 2023 Global Food Policy Report: Rethinking Food Crisis Responses – Considerations for Africa IFPRI Africa Regional Office JUN 22, 2023 - 9:00 TO 10:30AM EDT